2019
DOI: 10.3390/f10090727
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration in the Understory of Declining Overstory Trees Contributes to Soil Respiration Homeostasis along Succession in a Sub-Mediterranean Beech Forest

Abstract: Research Highlights: Tree decline can alter soil carbon cycling, given the close relationship between primary production and the activity of roots and soil microbes. Background and Objectives: We studied how tree decline associated to old age and accelerated by land-use change and increased drought in the last decades, affects soil properties and soil respiration (Rs). Materials and Methods: We measured Rs over two years around centennial European beech (Fagus sylvatica L.) trees representing a gradient of dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 65 publications
1
7
0
Order By: Relevance
“…In our experiment, drought relatively reduced Rs by 3.4%. This was consistent with previous studies on the semi-arid grassland ecosystem in Inner Mongolia and the Mediterranean ecosystem [14,49,[51][52][53]. In arid and semi-arid ecosystems, water availability is the primary factor influencing the productivity and carbon source for Rs.…”
Section: Effect Of Drought On Soil Respirationsupporting
confidence: 92%
“…In our experiment, drought relatively reduced Rs by 3.4%. This was consistent with previous studies on the semi-arid grassland ecosystem in Inner Mongolia and the Mediterranean ecosystem [14,49,[51][52][53]. In arid and semi-arid ecosystems, water availability is the primary factor influencing the productivity and carbon source for Rs.…”
Section: Effect Of Drought On Soil Respirationsupporting
confidence: 92%
“…Additionally, slope, orientation, altitude and soil depth were also measured in the same plots (Supplementary Material, Appendix S3, Table S3). For the description of the methods employed to measure total soil N see Rodrıǵuez-Calcerrada et al (2019); for the methods employed to measure the rest of abiotic variables see .…”
Section: Abiotic Variablesmentioning
confidence: 99%
“…The locations of background sampling locations were adjusted slightly upon collar installation to exclude local low points with a tendency to accumulate water and locations with shallow soils or exposed bedrock that prevented insertion of flux collars. Patches of understory vegetation may also contribute to soil F CO2 [35], and so were also avoided. After study trees were selected, six soil efflux collars were inserted at a distance of approximately one meter from the base of each tree.…”
Section: Data Collectionmentioning
confidence: 99%
“…However, counterexamples exist [10,31], and several chrono sequence studies have found reduced F CO2 with stand age in even-aged plantations [32,33], or no consistent relationship [34]. Rodríguez-Calcerrada et al, [35] tested for associations between visible crown health indicators and F CO2 in an open woodland in Spain but found that increased plant recruitment near declining trees offset potential reductions in F CO2 related to tree decline. The character of C supply could theoretically shift as trees age from active extrusion of labile root exudates by more productive trees to less bioavailable necrotic tissues, but the connection between local tree effects on F CO2 and tree senescence or health status has received little attention.…”
Section: Introductionmentioning
confidence: 99%